Uterine metastasis of lung adenocarcinoma under molecular target therapy with epidermal growth factor receptor tyrosine kinase inhibitors: A case report and review of the literature. Issue 2 (2nd November 2017) - Shibata, Mayu; Shizu, Masato; Watanabe, Kazuko; Takeda, Akihiro
Abstract: A 63‐year‐old woman presented with abnormal vaginal bleeding. Her disease history was significant, and included advanced lung adenocarcinoma with a deletion mutation in exon 19 of the epidermal growth factor receptor ( EGFR ) gene, which was managed by concurrent chemoradiotherapy, followed by molecular targeted therapy with tyrosine kinase inhibitors (TKIs) for a two‐year period. Contrast‐enhanced computed tomography showed the enlargement of a previously suspicious myoma node, with peripheral enhancement. Hemorrhagic necrosis was also observed on magnetic resonance imaging. Transabdominal hysterectomy and bilateral salpingo‐oophorectomy showed solitary intramyometrial metastatic lung adenocarcinoma with a second‐site T790M gatekeeper mutation in exon 20 of the EGFR gene. In conclusion, uterine metastasis from lung adenocarcinoma can present a diagnostic challenge. The possibility of lung cancer metastasis should be considered when a uterine mass increases in size during treatment. Molecular analysis of the EGFR gene to detect mutations could provide useful information for planning the treatment strategy.